Culture, Democracy and the Right to Make Art The British Community Arts Movement - Jeffers, Alison; Moriarty, Gerri (Bloomsbury Academic, 2017)
Based on the words and experiences of the people involved, this book tells the story of the community arts movement in the UK, and, through a series of essays, assesses its influence on present day participatory arts practices. Part I offers the first comprehensive account of the movement, its history, rationale and modes of working in England, Northern Ireland, Scotland and Wales; Part II brings the work up to the present, through a scholarly assessment of its influence on contemporary practice that considers the role of technologies and networks, training, funding, commissioning and curating socially engaged art today. The community arts movement was a well-known but little understood and largely undocumented creative revolution that began as part of the counter-cultural scene in the late 1960s. A wide range of art forms were developed, including large processions with floats and giant puppets, shadow puppet shows, murals and public art, events on adventure playgrounds and play schemes, outdoor events and fireshows. By the middle of the 1980s community arts had changed and diversified to the point where its fragmentation meant that it could no longer be seen as a coherent movement. Interviews with the early pioneers provide a unique insight into the arts practices of the time. Culture, Democracy and the Right to Make Art is not simply a history because the legacy and influence of the community arts movement can be seen in a huge range of diverse locations today. Anyone who has ever encountered a community festival or educational project in a gallery or museum or visited a local arts centre could be said to be part of the on-going story of the community arts. This book is open access and available on www.bloomsburycollections.com . It is funded by the University of Manchester.